2009
DOI: 10.1021/jf901484t
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with α-Amylase Inhibitor Wheat Albumin to High-Fat Diet-Induced Insulin-Resistant Rats Is Associated with Increased Expression of Genes Related to Fatty Acid Synthesis in Adipose Tissue

Abstract: It is well-known that insulin resistance induces lipid abnormalities by decreasing insulin actions in adipose tissue. This study examined the effects of inhibiting postprandial hyperglycemia/hyperinsulinemia, using the alpha-amylase inhibitor wheat albumin (WA), on the expression of genes related to fatty acid metabolism in the adipose tissue of high-fat diet-induced insulin-resistant rats. Postprandial glucose and insulin levels were significantly lower after oral starch loading with WA than with inactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A series of signaling molecules, such as glucose, insulin, and thyroid hormones affect the expression of ACCs through these transcriptional factors. For instance, high-carbohydrate diet induces ACC expression through ChREBP [ 26 ] or an insulin-mediated SREBP1 mechanism [ 27 ]. The ACC1 expression is also modulated at the translational level.…”
Section: Acetyl-coa Carboxylase Genes Expression Regulation and Pmentioning
confidence: 99%
“…A series of signaling molecules, such as glucose, insulin, and thyroid hormones affect the expression of ACCs through these transcriptional factors. For instance, high-carbohydrate diet induces ACC expression through ChREBP [ 26 ] or an insulin-mediated SREBP1 mechanism [ 27 ]. The ACC1 expression is also modulated at the translational level.…”
Section: Acetyl-coa Carboxylase Genes Expression Regulation and Pmentioning
confidence: 99%
“…This initiates starch digestion in the mouth and the small intestine, respectively, followed by amyloglucosidase action that cleaves the terminal α-1,6 and α-1,4 linkages, thereby releasing free glucose that is ready for intestinal absorption in the gut lumen (Voet & Voet, 2011). The commonly known dietary inhibitors of α-amylase are proteins in nature, belonging to the family of albumins (Murayama et al, 2009). In addition, some antioxidants that are usually found in oats are important substances such as proteins, peptides, and phenolic compounds which help in preventing human diseases by combating oxidative stress and reducing the levels and effects of biological free radicals (Emmons et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the suppression of postprandial hyperglycemia, the efficacy of indigestible dextrin or wheat albumin has been reported (14,15). Our previous study suggested that intake of kale (Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%